KONSEP PENDIDIKAN ISLAM PERSPEKTIF IBNU SINA - Rizky, Muh Rifqal Kaylafayza; Faizin, Moh; Rahmasari, Sita; Saputra, Wahyu Adi (TA'LIMUNA: Jurnal Pendidikan Islam, 2023)
Abstract: This study aims to analyze the dimensions of Islamic education from Ibn Sina's perspective and at the same time discover the concept of Islamic education from Ibn Sina's perspective. This type of research is library research. The results of this study are the concept of Islamic education according to Ibnu Sina including curriculum dimensions, educational method dimensions, educator dimensions, student dimensions, and punishment dimensions (education). The findings in this study are that Ibn Sina's concept of education is in line with his view of human beings, namely human beings who are nurtured from all potential within themselves in a balanced and comprehensive manner. This research has implications for strengthening the concept of Islamic education which has been initiated by Islamic education experts, especially those in Indonesia.